Multicenter randomized controlled trial of conventional versus laparoscopic surgery for colorectal cancer within an enhanced recovery programme: EnROL. - Kennedy, R; Francis, E; Wharton, R; Blazeby, J; Quirke, P; West, N; Dutton, S (American Society of Clinical Oncology, 2014)
PURPOSE: Laparoscopic resection and a multimodal approach known as an enhanced recovery program (ERP) have been major changes in colorectal perioperative care that have improved clinical outcomes for colorectal cancer resection. EnROL (Enhanced Recovery Open Versus Laparoscopic) is a multicenter randomized controlled trial examining whether the benefits of laparoscopy still exist when open surgery is optimized within an ERP. PATIENTS AND METHODS: Adults with colorectal cancer suitable for elective resection were randomly assigned at a ratio of 1:1 to laparoscopic or open surgery within an ERP, stratified by center, cancer site (colon v rectum), and age group (<66 v 66-75 v >75 years) using minimization. The primary outcome was physical fatigue at 1 month postsurgery. Secondary outcomes included hospital stay, complications, other patient-reported outcomes (PROs), and physical function. Patients and outcome assessors were blinded until 7 days postsurgery or discharge if earlier. Central independent and blinded pathologic assessment of surgical quality was undertaken. RESULTS: A total of 204 patients (laparoscopy, n=103; open surgery, n=101) were recruited from 12 UK centers from July 2008 to April 2012. One-month physical fatigue scores were similar in both groups (mean: laparoscopy, 12.28; 95% CI, 11.37 to 13.19 v open surgery, 12.05; 95% CI, 11.14 to 12.96; adjusted mean difference, -0.23; 95% CI, -1.52 to 1.07). Median total hospital stay was significantly shorter after laparoscopic surgery (median: laparoscopy, 5; interquartile range [IQR], 4 to 9 v open surgery, 7; IQR, 5 to 11 days; P=.033). There were no differences in other secondary outcomes or in specimen quality after central pathologic review. CONCLUSION: In patients treated by experienced surgeons within an ERP, physical fatigue and other PROs were similar in both groups, but laparoscopic surgery significantly reduced length of hospital stay.